2020
DOI: 10.1108/ecam-11-2019-0602
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for digital partnering of construction organisations – a Delphi study

Abstract: PurposeThe construction organisations in developing countries are lagging in digital technology usage; hence, they are still characterised by poor project delivery and technological backwardness. To checkmate this problem, partnering with other organisations was proposed, while critical factors needed for successful digital partnering of construction organisations were assessed.Design/methodology/approachThe study adopted a qualitative research approach. Delphi method was used to get experts' opinion on some i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 66 publications
(102 reference statements)
2
57
0
Order By: Relevance
“…We conducted this study to highlight the importance of sustainability in the procurement process through a research design including three stages of (1) literature review, (2) opinion survey, and (3) expert consensus. As a result of the first stage, it was found that although there are evident benefits for contractors both in the public and private sectors in practicing sustainability, evidence from previous research shows that it has not still become a permanent part of construction projects (Charmaz, 2014;Giles and Yates, 2014;Aghimien, Aigbavboa and Oke, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted this study to highlight the importance of sustainability in the procurement process through a research design including three stages of (1) literature review, (2) opinion survey, and (3) expert consensus. As a result of the first stage, it was found that although there are evident benefits for contractors both in the public and private sectors in practicing sustainability, evidence from previous research shows that it has not still become a permanent part of construction projects (Charmaz, 2014;Giles and Yates, 2014;Aghimien, Aigbavboa and Oke, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested in the literature that after consolidating the individual expert feedback, the results can be sent to participants to review the consolidated outcomes and validate them (Aghimien, Aigbavboa and Oke, 2020). Participants were invited via email to review the elicited codes and themes representing essential roles that PMOs undertake to implement sustainability in the procurement process.…”
Section: ) Validationmentioning
confidence: 99%
“…Process-centric strategic consideration suggests systematic implementation of digital technologies and has been found to foster DT in construction (Li et al, 2019;Aghimien et al, 2020b). This strategic consideration aligns the implementation of digital technologies procedurally with the construction project lifecycle phases (Koseoglu et al, 2019;Morgan, 2019), for instance, initially implementing BIM in the design and construction phases and later implementing the tool at the building operation phase.…”
Section: Processmentioning
confidence: 99%
“…Taking an example of BIM implementation, BIM champions are distinguished from adopters-only by emphasizing institutional outcomes beyond implementationonly (Azzouz and Papadonikolaki, 2020), such as digital knowledge networking (Azzouz and Papadonikolaki, 2020;Hetemi et al, 2020). Digital champions can be construction and project leaders who imbibe a strong commitment to implement digital technologies even when inconvenient (Chen, 2019a;Aghimien et al, 2020b). Such commitment can be exemplary for operation-level employees in construction (Berlak et al, 2020) and has been found to motivate them to become digital champions (Bonanomi et al, 2019).…”
Section: Digital Championsmentioning
confidence: 99%
See 1 more Smart Citation